Changing children's eating behaviour - A review of experimental research. (1st June 2017) - DeCosta, Patricia; Møller, Per; Frøst, Michael Bom; Olsen, Annemarie
Abstract: The interest in children's eating behaviours and how to change them has been growing in recent years. This review examines the following questions: What strategies have been used to change children's eating behaviours? Have their effects been experimentally demonstrated? And, are the effects transient or enduring? Medline and Cab abstract (Ovid) and Web of Science (Thomson Reuters) were used to identify the experimental studies. A total of 120 experimental studies were identified and they are presented grouped within these 11 topics; parental control, reward, social facilitation, cooking programs, school gardens, sensory education, availability and accessibility, choice architecture and nudging, branding and food packaging, preparation and serving style, and offering a choice. In conclusion, controlling strategies for changing children's eating behaviour in a positive direction appear to be counterproductive. Hands-on approaches such as gardening and cooking programs may encourage greater vegetable consumption and may have a larger effect compared to nutrition education. Providing children with free, accessible fruits and vegetables have been experimentally shown to positively affect long-term eating behaviour. The authors recommend future research to examine how taste and palatability can positively affect children's attitudes and eating behaviour.